MUTASYABIH : MAKNA ISTAWA DALAM AL-QUR`AN - Ahmad Ridwan Nasution; M. Iqbal Irham (MIYAH : Jurnal Studi Islam, 2022)
Abstract: The Ayat Mutasyabih is frequently become interesting materials of discussion among Muslims due to the unclear content of its meaning. Moreover, if the Ayat is related to the name of Allah or monotheism, it can lead to disbelievers. The word that is most often debated by scholars today is the word Istawa, because this word in the Qur'an is directly attributed to Allah. There are various ways by which scholars interpret the ayat, some interpret it as it is without interpreting it to other meanings, and some the other way around. So this is the main object of study in this paper. This paper was written using the literature study method, namely by looking at books related to the title of this paper. From the sources obtained, it can be concluded that the scholars in understanding the word istawa are divided into two groups, namely groups that do not seek other meanings just as they are without questioning, simulating, and assuming anything. The second group is the scholars who are looking for Takwil from the word IstawaKeyword: Mutasyabih, Takwil, Istawa.